High Sensitivity and Label-Free Detection of the SARS-CoV-2 S1 Protein Using a Terahertz Meta-Biosensor - Niu, Qiang; Zhang, Ran; Yang, Yuping (Frontiers in Physics, 2022)
High-sensitivity and quantitative detection of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) spike protein (S protein) is of great significance for diagnosis and treatment of coronaviruses. Here, we utilized terahertz time-domain spectroscopy (THz-TDS) integrated with metamaterial (MM)-based biosensor and biological modification technology to demonstrate a high accuracy and label-free detection of SARS-CoV-2 S1 protein by comparing the changes of dielectric environment before and after binding the S1 protein. To confirm the sensing characteristics observed in the experiments and provide a further insight into the sensing mechanisms, we performed numerical simulations through varying the thickness, quantity, position, and refractive index of analyte aggregates. The sensitivity increases with the increase of the number of gaps and the amount of analyte near the gaps, which convincingly proves that the frequency shift and sensing performance are strongly influenced by the field enhancement and the near-field coupling at the gap area.